Efektivitas Model Pembelajaran Kooperatif dalam Meningkatkan Kemampuan Interpersonal dan Prestasi Belajar Kalkulus Diferensial - Husriani Husain; Chusnul Chatimah Azis; Ahmad Talib (FKIP Universitas Mataram, 2026)
Differential Calculus courses at the Mathematics Education Study Program of Institut Turatea Indonesia face challenges including low conceptual understanding and limited student interaction due to teacher-centered learning. This study aimed to examine the effectiveness of the STAD-type cooperative learning model in improving students' interpersonal skills and academic achievement in Differential Calculus. A quantitative approach with a One Group Pretest–Posttest design was employed, involving 17 students selected through total sampling. Data were collected using academic achievement tests, an interpersonal skills questionnaire, learning implementation and student activity observation sheets, and a student response questionnaire, then analyzed using the Shapiro–Wilk normality test, Paired Sample t-test, and effect size calculation (Cohen's d). The results showed that learning implementation was accomplished (mean = 3.49) with excellent student activity (mean = 3.80). Cooperative learning had a significant effect on academic achievement (t = −19.439; p < 0.001; d = 4.02) and interpersonal skills (t = −12.286; p < 0.001; d = 2.50), both classified as very large effect. Students demonstrated positive responses with a mean score of 3.41. These findings indicate that the STAD-type cooperative learning model is effective in improving students' interpersonal skills and academic achievement in Differential Calculus.